Highlighting the issues in making an informed interaction-based decision in industrial ecosystems - Hussain, Omar; Dillon, Tharam S.; Chang, Elizabeth; Hussain, Farookh Khadeer (IEEE, 2008)
In the literature, the notion of trust has been widely discussed and various approaches have been proposed to assess and quantify it, in order to take it into consideration when making an interaction-based decision in industrial ecosystems. At the same time, the notion and importance of risk have been widely ignored and not been acknowledged as an important factor to consider, along with trust; while making an interaction-based decision. Although there are approaches in the literature which attempt to quantify risk in the domain of a business interaction in industrial ecosystems, none of them proposes a methodology by which the initiating agent of the interaction can ascertain and determine all the various concepts that are expressed by risk in that domain, and then utilize it to make an informed interaction-based decision. In this paper we present an evaluation of the approaches from the literature and highlight the issues which need to be addressed in order to assist the initiating agent of the interaction in making an informed interaction-based decision with another agent in Industrial ecosystems.